Ekphrasis and Narrative, or the Ideological Critique of Artworks: Alma-Tadema, Ennio Flaiano and the Legacy of Heliogabalus - Guido Mattia Gallerani (Linguae &: Rivista di Lingue e Culture Moderne, 2017)
Just before his death in 1972, the Italian writer Ennio Flaiano wrote a short story entitled “La penultima cena” (The Penultimate Supper) in which Sir Lawrence Alma-Tadema’s painting The Roses of Heliogabalus (1888) is referenced and the “myth” of Heliogabalus itself comes to play a fundamental role in the construction of the narrative. Though the scene recreated by the characters in Flaiano’s short story may be interpreted as a mise en abyme, through the transformation of Alma-Tadema’s original image using different modes of writing – in particular narrative dialogues and ekphrasis – Flaiano actually critiques an elitist and anti-historical use of art in literature. Building on a reference that the narrator makes to the Decameron, the article shows how the ekphrasis hosts an ideological conflict that opposes the narrator’s interpretation of Heliogabalus’s feast to the one reproduced and staged during a fancy dinner held by members of Rome’s high-society.